1990
DOI: 10.1159/000310145
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Corticosteroid Therapy in Vogt-Koyanagi-Harada Disease

Abstract: We evaluated the significance of corticosteroid therapy on 47 new patients with Vogt-Koyanagi-Harada disease examined in the Uveitis Survey Clinic of the Hokkaido University Hospital. All patients were treated with topical corticosteroids, with or without systemic corticosteroids. 18 patients received systemic corticosteroid as pulse therapy, 20 patients received high-dose corticosteroid starting with prednisolone 200 mg, 2 patients received conventional-dose corticosteroid and 7 patients received no systemic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0
3

Year Published

1994
1994
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(38 citation statements)
references
References 3 publications
2
33
0
3
Order By: Relevance
“…3,6 In cases with severe ocular inflammation associated with acute VKH, intravenous pulse steroid therapy has also been advocated. 5,12 A recent study by Read et al, 7 however, showed no detectable difference in the visual outcome and complications in the route of corticosteroid administration, and therefore we preferred to use oral corticosteroid for the patients as they do not require hospitalization. The therapeutic effect of systemic corticosteroid lies mainly on its anti-inflammatory and immunosuppressant properties.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…3,6 In cases with severe ocular inflammation associated with acute VKH, intravenous pulse steroid therapy has also been advocated. 5,12 A recent study by Read et al, 7 however, showed no detectable difference in the visual outcome and complications in the route of corticosteroid administration, and therefore we preferred to use oral corticosteroid for the patients as they do not require hospitalization. The therapeutic effect of systemic corticosteroid lies mainly on its anti-inflammatory and immunosuppressant properties.…”
Section: Discussionmentioning
confidence: 96%
“…2,3 During the acute stage of VKH, treatment usually requires aggressive systemic corticosteroid therapy to prevent irreversible damage causing visual loss. [5][6][7] However, recurrence of inflammation is not uncommon after cessation of corticosteroid therapy, especially when the steroid is tapered too rapidly. 6 Therefore, in acute VKH, it has been recommended to maintain high dose oral corticosteroid therapy and taper it gradually over at least 3-6 months.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, neurological signs and dysacousia are quite common (74-76%) among Japanese patients [23,28], while intertegumentary signs are more often seen in Chinese patients (39-41%) [29]. When looking at ocular manifestations, studies conducted on South American patients are concordant in rating a optic disc swelling occurrence significantly lower than in Asian patients (8,6% -9% versus 50-73%, respectively) [26][27][28][29][30] Giordano et al) [26,30]. Response to therapy and complication rates are reported to be similar among ethnic groups [26].…”
Section: Discussionmentioning
confidence: 99%
“…Лечение синдрома Фогта-Коянаги-Харада ба-зируется на системном, агрессивном применении кортикостероидов и иммуносупрессоров (цитоста-тики) [7,10,11].…”
Section: вестник офтальмологии 3 2015unclassified
“…Локальное применение кортикостероидов (дек-саметазон) оказывает не только противовоспали-тельное, но и иммуносупрессивное действие [10,12], поэтому такая схема не должна использоваться в лечении аутоиммунных воспалительных процес-сов с развитием панувеита. Прямыми показаниями к системному применению кортикостероидов слу-жат поражения органа зрения и увеаретинального тракта, запущенные или осложненные случаи за-дних увеитов или панувеитов.…”
Section: вестник офтальмологии 3 2015unclassified